Evaluasi Manajemen Risiko Teknologi Informasi menggunakan Standar Cobit 5 IT Risk pada PTPN X Pabrik Gula Meritjan Kediri - Fakhri Ivan Alfiansyah; Buce Trias Hanggara; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
To help running business processes and make effective and efficient decisions, Finance and General Affairs Division of PG. Meritjan Kediri PTPN X uses SAP (System Application and Product in Data Processing). Risk management applied to PG. Meritjan Kediri uses ISO 9001: 2015 and ISO 14001: 2015 standards to deal with risks that interfere with the implementation of the company's business processes. The APO12 (Risk Management) and EDM03 (Ensure Risk Optimation) process domains in the COBIT 5 framework are used in the evaluation of information technology risk management in order to know the extent of the achievements of the IT risk management in the financial and general sections of PG. Meritjan Kediri. Data collected using questionnaires, making direct observations, and conducting interviews with related parties. Meanwhile, the stage for conducting the evaluation process consists of analyzing the capability level, gap and risk assessment. Risk assessment is carried out to identify risks and assess their impact. Capability level analysis resulted in level 2 in the APO12 and EDM03 process domain, 11 steps and mitigation strategies, and 11 recommendations. These results are used as the basis used to improve IT risk management implemented by the finance and general department of PG.Meritjan Kediri.